Narrate Mozambique: the colonial experience trail - Kütter, Cíntia Acosta (Faculdade de Ciências e Letras - Unesp - Araraquara., 2018)
The present work aim to analyze the experience of the colonial trail in the novel Crônica da Rua 513. 2, written by the Mozambican João Paulo Borges Coelho. When we think of the fictional text in the chronicle format, as the novelist intends, we find that he does it in this way so that we also look at the different parts in which this postcolonial society has been divided. We will also think about the importance of memory for this country that has so little time known the term “independence”, although it took so long to arrive, it is important to remember, so that what was important is not forgotten. With this, we will reflect on the importance of the trace and the memory present in his literary work and in the history of Mozambique.